Zigbee over tinyos: Implementation and experimental challenges - Cunha, André (2008)
The IEEE 802.15.4/Zigbee protocols are a promising technology for Wireless Sensor Networks (WSNs). This paper shares our experience on the implementation and use of these protocols and related technologies in WSNs. We present problems and challenges we have been facing in implementing an IEEE 802.15.4/ZigBee stack for TinyOS in a two-folded perspective: IEEE 802.15.4/ZigBee protocol standards limitations (ambiguities and open issues) and technological limitations (hardware and software). Concerning the former, we address challenges for building scalable and synchronized multi-cluster ZigBee networks, providing a trade-off between timeliness and energy-efficiency. On the latter issue, we highlight implementation problems in terms of hardware, timer handling and operating system limitations. We also report on our experience from experimental test-beds, namely on physical layer aspects such as coexistence problems between IEEE 802.15.4 and 802.11 radio channels.